Method for improving electrocaloric effect of barium titanate-based ferroelectric perovskite electrocaloric material

By introducing multiple elements into barium titanate-based ferroelectric perovskite materials and co-doping synthesis, the problem of insufficient electric card strength in the prior art is solved, and high electric card is achieved The effect and wide temperature range significantly improve the refrigeration performance.

CN119430913AActive Publication Date: 2025-02-14SHANGHAI JIAOTONG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411723288.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-14
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Existing inorganic ferroelectric materials cannot achieve super-large electric card strength under high electric fields, and it is difficult to take into account the large electric card effect and wide working temperature range.

Method used

By introducing precursors such as zirconium, hafnium, tin, strontium, calcium into barium titanate-based ferroelectric perovskite materials, using multi-element co-doping method to perform solid phase synthesis and high-temperature sintering to prepare high-electric cards Ceramic material of performance.

Benefits of technology

It significantly improves the strength of the electric card and the polarization freedom of the material, widens the execution temperature range of the material, and has a large electric card effect within a wide temperature range near room temperature, simplifies the design of the electric card refrigeration equipment and Improved refrigeration capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430913A_ABST
    Figure CN119430913A_ABST
Patent Text Reader

Abstract

The invention relates to a method for improving the electrocaloric effect of a ferroelectric perovskite material, which comprises the following steps: weighing a Ba source, a Sr source, a Ca source, an Hf source, a Sn source, a Zr source and a Ti source, uniformly mixing according to a stoichiometric ratio, and pre-sintering to obtain (BaxSryCazA (1-x-y-z) (HfaSnbZrcTidB (1-a-b-c-d) O3 powder; finely grinding, mixing with a binder, granulating, forming, aging, and removing plastic to obtain a ceramic biscuit; according to the barium titanate-based ferroelectric perovskite electrocaloric material with the high electrocaloric performance and the preparation method thereof, barium titanate ceramic serves as a matrix, precursors of elements such as zirconium, hafnium, tin, strontium and calcium are introduced into solid-phase method synthesis, a BaTiO3 material is doped and substituted at A and B positions by multiple elements at the same time, and the barium titanate-based ferroelectric perovskite electrocaloric material with the high electrocaloric performance is obtained after blending and high-temperature sintering. The method is simple in preparation condition, mature in process, low in cost and high in reliability. Under the induction of an electric field, huge entropy change and an electrocaloric effect are generated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a technology in the field of all-solid-state refrigeration materials, in particular to a method for improving the electrocaloric effect of a barium titanate-based ferroelectric perovskite electrocaloric material. Background Art

[0002] The electrocaloric effect is an important development direction for the development of new refrigeration equipment, and doping is an effective means to improve the performance of electrocaloric materials. However, the existing doping technology has no major changes to the overall material structure due to its small doping amount or single doping type. The electrocaloric effect is essentially the thermal effect caused by the transition of the polarization structure between order and disorder under the action of an electric field. Therefore, this multi-element co-doping method can significantly improve the electrocaloric effect. Summary of the invention

[0003] The present invention aims at the problem that inorganic ferroelectric materials cannot achieve ultra-large electrocaloric strength under high electric field in the prior art and the problem that existing inorganic electrocaloric materials are difficult to take into account both large electrocaloric effect and wide operating temperature range. A method for improving the electrocaloric effect of ferroelectric perovskite materials is proposed. Barium titanate ceramics are used as a matrix. Precursors of zirconium, hafnium, tin, strontium, calcium and other elements are introduced in solid phase synthesis. Multi-element doping replaces BaTiO3 materials at positions A and B at the same time. The finished product is obtained by high-temperature sintering after blending. The method has simple preparation conditions, mature process, low cost and high reliability. Under the induction of electric field, huge entropy change and electrocaloric effect are generated.

[0004] The present invention is achieved through the following technical solutions:

[0005] The present invention relates to a method for improving the electrocaloric effect of a barium titanate-based ferroelectric perovskite electrocaloric material, comprising weighing a Ba source, a Sr source, a Ca source, a Hf source, a Sn source, a Zr source, and a Ti source, mixing them uniformly according to a stoichiometric ratio, and pre-sintering to obtain (Ba x Sr y Ca z A 1-x-y-z )(Hf a Sn b Zr c Ti d B 1-a-b-c-d )O3 powder; after fine grinding and mixing with a binder, granulation is carried out, and then molding, aging, and plastic removal treatment are carried out to obtain a ceramic green body; finally, by sintering, a barium titanate-based ferroelectric perovskite electric caloric material with high electric caloric performance is obtained, wherein: 0.6≤x<1, 0<y≤0.4, 0<z≤0.4, 0<a≤0.3, 0<b≤0.3, 0<c≤0.3, 0.7≤d<1.

[0006] The stoichiometric ratio refers to the proportion of each element (Ba x Sr y Caz A 1-x-y-z )(Hf a Sn b Zr c Ti d B 1-a-b-c-d )Chemical composition ratio of O3 material.

[0007] The Ba source, Sr source, Ca source, Hf source, Sn source, Zr source and Ti source are oxides containing the elements or salts and hydroxides that can be decomposed into the required oxides at high temperatures, such as BaO, SrO, CaO or Ba(OH)2, Sr(OH)2, Ca(OH)2, etc.; preferably BaCO3, SrCO3, CaCO3, HfO2, SnO2, ZrO2 and TiO2.

[0008] The pre-sintering process is to heat the mixture in an oxygen, air or nitrogen atmosphere at 2-5°C / min. -1 The heating rate is raised to 1100-1400°C, kept warm for 1-6 hours, preferably for 2-4 hours, and then cooled with the furnace.

[0009] The binder is polyvinyl alcohol, polyethylene glycol, polystyrene, methyl cellulose or a combination thereof, and its usage is 5-10wt% of the mass of the ceramic powder.

[0010] The aging refers to aging at room temperature for 22 to 48 hours, preferably 22 to 26 hours.

[0011] The plastic removal refers to: in an oxygen or air atmosphere, at a temperature not higher than 2℃min -1 The heating rate is increased to 600-800°C and kept warm for 1-3 hours. The discharge temperature is preferably 650-750°C.

[0012] The sintering process is to heat the mixture in an oxygen, air or nitrogen atmosphere at 2-5°C / min. -1 The heating rate is raised to 1300-1500°C, preferably 1300-1400°C, and kept warm for 1-6 hours. After sintering, the furnace is cooled to room temperature.

[0013] The present invention relates to a barium titanate-based ferroelectric perovskite electrocaloric material prepared by the above method, specifically (Ba 0.8 Sr 0.199 Ca 0.001 )(Hf 0.025 Sn 0.025 Zr 0.025 Ti 0.925 )O3、(Ba 0.8 Sr 0.2 )(Hf 0.02 Sn 0.02 Zr0.02 Ti 0.94 )O3、 (Ba 0.8 Sr 0.199 Ca 0.001 )(Hf 0.03 Sn 0.03 Zr 0.03 Ti 0.91 )O3 or (Ba 0.905 Sr 0.09 Ca 0.005 )(Hf 0.0307 Sn 0.0307 Zr 0.0307 Ti 0.9079 )O3.

[0014] The present invention relates to an application of the above-mentioned barium titanate-based ferroelectric perovskite electrocaloric material, which is used for preparing an electrode layer of a solid-state refrigeration element.

[0015] The application is specifically as follows: magnetron sputtering gold is plated on the surface of a barium titanate-based ferroelectric perovskite electrocaloric material, and a gold electrode layer is obtained after deposition in a vacuum at a current of 0.2 to 0.3 nA for 30 to 180 seconds. Technical Effects

[0016] The present invention refines the ferroelectric domains in the inorganic ferroelectric ceramics, increases the substrate entropy that can induce the electrocaloric effect, and optimizes the electrocaloric strength. Compared with the prior art, the present invention significantly improves the electrocaloric strength while refining the ferroelectric domains in the inorganic ferroelectric ceramics, significantly increases the domain wall density, improves the polarization freedom of the material, increases the substrate entropy that can induce the electrocaloric effect, and optimizes the electrocaloric strength, especially under the action of a high electric field. The temperature stability of the electrocaloric effect is improved. Multi-element co-doping allows the electric dipole moments of various properties dispersed in the material to exist simultaneously, which broadens the execution temperature range of this material, so that it has a large electrocaloric effect in a wide temperature range near room temperature. The use of the electrocaloric refrigeration material of the present invention can simplify the design of the electrocaloric refrigeration equipment and improve the refrigeration capacity of the electrocaloric refrigerator. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscope morphology image of the high electrocaloric performance ceramic sheet of Example 1;

[0018] Figure 2 Schematic diagram of dielectric temperature spectrum of high electrocaloric performance ceramic material of Example 1;

[0019] Figure 3 This is a schematic diagram of the hysteresis loop of the high electrocaloric performance ceramic material of Example 1;

[0020] Figure 4This is the temperature variation curve of the electrocaloric effect of the high electrocaloric performance ceramic material of Example 1 as the temperature changes.

[0021] Figure 5 Schematic diagram of the electrocaloric effect temperature variation curve of the high electrocaloric performance ceramic materials of Examples 1-4 as the electric field intensity changes. DETAILED DESCRIPTION Example 1

[0022] Ferroelectric ceramic materials (Ba 0.8 Sr 0.199 Ca 0.001 )(Hf 0.025 Sn 0.025 Zr 0.025 Ti 0.925 ) Preparation of O3:

[0023] 1) BaCO3, SrCO3, CaCO3, HfO2, SnO2, ZrO2, and TiO2 are used as raw materials, prepared according to the stoichiometric ratio shown in the chemical formula, and mixed by wet ball milling. The raw materials: ball mill: ethanol = 1: (2-10): (0.7-1.2) are mixed for 16 hours, and zirconium balls are selected as ball mills. After drying, the mixed powder blocks are pressed into blocks and heated at 2 ° C min in air atmosphere. -1 The heating rate was raised to 1200℃ for pre-sintering, and after keeping the temperature for 3h, it was cooled with the furnace, crushed and passed through a 40-mesh sieve to obtain (Ba 0.8 Sr 0.199 Ca 0.001 )(Hf 0.025 Sn 0.025 Zr 0.025 Ti 0.925 )O3 powder; and then use the stirring ball milling method for secondary ball milling to make the particle size fine, the stirring ball milling is carried out according to the mass ratio of raw material: ball mill: ethanol = 1:10:2, and the ball milling is dried and sieved after 3h.

[0024] 2) The (Ba) obtained in step 1) 0.8 Sr 0.199 Ca 0.001 )(Hf 0.025 Sn 0.025 Zr 0.025 Ti 0.925 )O3 powder was finely ground by stirring ball milling for 3 hours, according to the mass ratio of raw material: ball mill: ethanol = 1: (2-10): (0.7-1.2), dried and sieved, and then 9wt% polyvinyl alcohol (PVA) binder was added and granulated, followed by pressing and molding. After aging for 24 hours, it was ground again in a mortar and sieved through a 40-mesh sieve. The obtained powder was pressed into discs with a diameter of 12.7 mm and a thickness of 2 mm, and then heated to 700°C in an air atmosphere for 2 hours to obtain a ceramic blank.

[0025] 3) Place the ceramic body in an alumina crucible, cover it with calcined powder of the same composition, close the lid, and incubate in air at 2°C min -1 The heating rate is increased to 1380°C and kept at this temperature for 2 hours. After cooling in the furnace, a barium titanate-based ferroelectric ceramic material with high electrocaloric performance is obtained.

[0026] This embodiment is further based on the application of the above-mentioned barium titanate-based ferroelectric ceramic material. The ceramic material sample sintered in step 3 is ground into a ceramic sheet with a thickness of 0.15 mm. After ultrasonic cleaning and drying, the upper and lower surfaces are magnetron sputtered with gold, and the gold electrode layer is obtained after deposition in a vacuum for 90 seconds with a current of 0.25 nA.

[0027] The electrocaloric effect heat flow test of ceramic components was carried out, and the following results were obtained: Figure 2 The dielectric temperature spectrum of the ferroelectric ceramic of this embodiment is shown. It can be seen from the figure that this material has a high dielectric constant at room temperature and has multiple dielectric peaks near room temperature, indicating its potential for electroinduced phase transition.

[0028] like Figure 3 , which is a schematic diagram of the hysteresis loop of the ferroelectric ceramic element prepared in this embodiment at room temperature;

[0029] like Figure 4 The figure shows the electrocaloric effect temperature variation curve of the ferroelectric ceramic material prepared in this embodiment at different temperatures and electric field strengths. It can be seen from the figure that this ceramic material has a wide operating temperature range.

[0030] like Figure 5 The graphs are as follows: the curves of the electrocaloric temperature change of the ceramic element prepared in this embodiment as a function of the electric field strength, and the comparison with other embodiments (i.e., different component designs). It can be seen from the graphs that the multi-element coexisting ceramic material designed by this method has a high electrocaloric effect strength. Example 2

[0031] Ferroelectric ceramic materials (Ba 0.8 Sr 0.2 )(Hf 0.02 Sn 0.02 Zr 0.02 Ti 0.94 ) Preparation of O3:

[0032] 1) BaCO3, SrCO3, HfO2, SnO2, ZrO2, and TiO2 are used as raw materials, prepared according to the stoichiometric ratio shown in the chemical formula, and mixed by wet ball milling. The raw materials: ball mill: ethanol = 1: (2-10): (0.7-1.2) are mixed for 16 hours, and zirconium balls are selected as ball mills. After drying, the mixed powder blocks are pressed into blocks and heated at 2 ° C min in air atmosphere. -1 The heating rate was raised to 1200℃ for pre-sintering, and after keeping the temperature for 3h, it was cooled with the furnace, crushed and passed through a 40-mesh sieve to obtain (Ba 0.8 Sr 0.2 )(Hf 0.02 Sn 0.02 Zr 0.02 Ti 0.94 )O3 powder; and then use the stirring ball milling method for secondary ball milling to make the particle size fine, the stirring ball milling is carried out according to the mass ratio of raw material: ball mill: ethanol = 1:10:2, and the ball milling is dried and sieved after 3h.

[0033] 2) The (Ba) obtained in step 1) 0.8 Sr 0.2 )(Hf 0.02 Sn 0.02 Zr 0.02 Ti 0.94 )O3 powder was finely ground by stirring ball milling for 3 hours, according to the mass ratio of raw material: ball mill: ethanol = 1: (2-10): (0.7-1.2), dried and sieved, and then 9wt% polyvinyl alcohol (PVA) binder was added and granulated, followed by pressing and molding. After aging for 24 hours, it was ground again in a mortar and sieved through a 40-mesh sieve. The obtained powder was pressed into discs with a diameter of 12.7 mm and a thickness of 2 mm, and then heated to 700°C in an air atmosphere for 2 hours to obtain a ceramic blank.

[0034] 3) Place the ceramic body in an alumina crucible, cover it with calcined powder of the same composition, close the lid, and incubate in air at 2°C min -1 The heating rate is increased to 1380°C and kept at this temperature for 2 hours. After cooling in the furnace, a barium titanate-based ferroelectric ceramic material with high electrocaloric performance is obtained.

[0035] This embodiment is further based on the application of the above-mentioned barium titanate-based ferroelectric ceramic material. The ceramic material sample sintered in step 3 is ground into a ceramic sheet with a thickness of 0.15 mm. After ultrasonic cleaning and drying, the upper and lower surfaces are magnetron sputtered with gold, and the gold electrode layer is obtained after deposition in a vacuum for 90 seconds with a current of 0.25 nA.

[0036] The electrocaloric effect temperature change test results of this embodiment and the comparison with the results of other embodiments can be seen in Figure 5 . Example 3

[0037] Ferroelectric ceramic materials (Ba 0.8 Sr 0.199 Ca 0.001 )(Hf 0.03 Sn 0.03 Zr 0.03 Ti 0.91 ) Preparation of O3:

[0038] 1) BaCO3, SrCO3, CaCO3, HfO2, SnO2, ZrO2, and TiO2 are used as raw materials, prepared according to the stoichiometric ratio shown in the chemical formula, and mixed by wet ball milling. The raw materials: ball mill: ethanol = 1: (2-10): (0.7-1.2) are mixed for 16 hours, and zirconium balls are selected as ball mills. After drying, the mixed powder blocks are pressed into blocks and heated at 2 ° C min in air atmosphere. -1 The heating rate was raised to 1200℃ for pre-sintering, and after keeping the temperature for 3h, it was cooled with the furnace, crushed and passed through a 40-mesh sieve to obtain (Ba 0.8 Sr 0.199 Ca 0.001 )(Hf 0.03 Sn 0.03 Zr 0.03 Ti 0.91 )O3 powder; and then use the stirring ball milling method for secondary ball milling to make the particle size fine, the stirring ball milling is carried out according to the mass ratio of raw material: ball mill: ethanol = 1:10:2, and the ball milling is dried and sieved after 3h.

[0039] 2) The (Ba) obtained in step 1) 0.8 Sr 0.199 Ca 0.001 )(Hf 0.03 Sn 0.03 Zr 0.03 Ti 0.91 )O3 powder was finely ground by stirring ball milling for 3 hours, according to the mass ratio of raw material: ball mill: ethanol = 1: (2-10): (0.7-1.2), dried and sieved, and then 9wt% polyvinyl alcohol (PVA) binder was added and granulated, followed by pressing and molding. After aging for 24 hours, it was ground again in a mortar and sieved through a 40-mesh sieve. The obtained powder was pressed into discs with a diameter of 12.7 mm and a thickness of 2 mm, and then heated to 700°C in an air atmosphere for 2 hours to obtain a ceramic blank.

[0040] 3) Place the ceramic body in an alumina crucible, cover it with calcined powder of the same composition, close the lid, and incubate in air at 2°C min -1 The heating rate is increased to 1380°C and kept at this temperature for 2 hours. After cooling in the furnace, a barium titanate-based ferroelectric ceramic material with high electrocaloric performance is obtained.

[0041] This embodiment is further based on the application of the above-mentioned barium titanate-based ferroelectric ceramic material. The ceramic material sample sintered in step 3 is ground into a ceramic sheet with a thickness of 0.15 mm. After ultrasonic cleaning and drying, the upper and lower surfaces are magnetron sputtered with gold, and the gold electrode layer is obtained after deposition in a vacuum for 90 seconds with a current of 0.25 nA.

[0042] The electrocaloric effect temperature change test results of this embodiment and the comparison with the results of other embodiments can be seen in Figure 5 . Example 4

[0043] Ferroelectric ceramic materials (Ba 0.905 Sr 0.09 Ca 0.005 )(Hf 0.0307 Sn 0.0307 Zr 0.0307 Ti 0.9079 ) Preparation of O3:

[0044] 1) BaCO3, SrCO3, CaCO3, HfO2, SnO2, ZrO2, and TiO2 are used as raw materials, prepared according to the stoichiometric ratio shown in the chemical formula, and mixed by wet ball milling. The raw materials: ball mill: ethanol = 1: (2-10): (0.7-1.2) are mixed for 16 hours, and zirconium balls are selected as ball mills. After drying, the mixed powder blocks are pressed into blocks and heated at 2 ° C min in air atmosphere. -1 The heating rate was raised to 1200℃ for pre-sintering, and after keeping the temperature for 3h, it was cooled with the furnace, crushed and passed through a 40-mesh sieve to obtain (Ba 0.905 Sr 0.09 Ca 0.005 )(Hf 0.0307 Sn 0.0307 Zr 0.0307 Ti 0.9079 )O3 powder; and then use the stirring ball milling method for secondary ball milling to make the particle size fine, the stirring ball milling is carried out according to the mass ratio of raw material: ball mill: ethanol = 1:10:2, and the ball milling is dried and sieved after 3h.

[0045] 2) The (Ba) obtained in step 1) 0.905 Sr 0.09 Ca 0.005 )(Hf 0.0307 Sn 0.0307 Zr 0.0307 Ti 0.9079)O3 powder was finely ground by stirring ball milling for 3 hours, according to the mass ratio of raw material: ball mill: ethanol = 1: (2-10): (0.7-1.2), dried and sieved, and then 9wt% polyvinyl alcohol (PVA) binder was added and granulated, followed by pressing and molding. After aging for 24 hours, it was ground again in a mortar and sieved through a 40-mesh sieve. The obtained powder was pressed into discs with a diameter of 12.7 mm and a thickness of 2 mm, and then heated to 700°C in an air atmosphere for 2 hours to obtain a ceramic blank.

[0046] 3) Place the ceramic body in an alumina crucible, cover it with calcined powder of the same composition, close the lid, and incubate in air at 2°C min -1 The heating rate is increased to 1380°C and kept at this temperature for 2 hours. After cooling in the furnace, a barium titanate-based ferroelectric ceramic material with high electrocaloric performance is obtained.

[0047] This embodiment is further based on the application of the above-mentioned barium titanate-based ferroelectric ceramic material. The ceramic material sample sintered in step 3 is ground into a ceramic sheet with a thickness of 0.15 mm. After ultrasonic cleaning and drying, the upper and lower surfaces are magnetron sputtered with gold, and the gold electrode layer is obtained after deposition in a vacuum for 90 seconds with a current of 0.25 nA.

[0048] The electrocaloric effect temperature change test results of this embodiment and the comparison with the results of other embodiments can be seen in Figure 5 .

[0049] like Figure 5 The figure shows the change in the electrocaloric refrigeration temperature of electrocaloric ceramics with different components. The preferred components shown in Example 1 have better electrocaloric refrigeration performance than Examples 2-4. This set of data proves the important role of components in regulating the electrocaloric refrigeration performance of ferroelectric ceramic materials, and the preferred components can significantly improve the performance.

[0050] Compared with the existing ceramic component design, the present invention adopts a multi-element co-doping material structure control method, and introduces multiple elements into the material at the same time to promote the increase of the polarization entropy of the electrocaloric ceramic, thereby improving the electrocaloric refrigeration performance. The barium titanate-based lead-free ferroelectric ceramic material provided by the present invention has excellent electrocaloric performance and good temperature stability. The electrocaloric strength of the selected component is greater than 0.5K m MV -1 The execution temperature range is greater than 30K, and the optimal composition (x=0.8, y=0.199, z=0.001, a=0.025, b=0.025, c=0.025, d=0.925) has an electrocaloric strength of up to 1K m MV -1 , the temperature range is greater than 60K near room temperature. -1 It has high electrocaloric effect and excellent temperature stability under low electric field strength.

[0051] The above-mentioned specific implementation can be partially adjusted in different ways by those skilled in the art without departing from the principle and purpose of the present invention. The protection scope of the present invention shall be based on the claims and shall not be limited by the above-mentioned specific implementation. Each implementation scheme within its scope shall be subject to the constraints of the present invention.

Claims

1. A method for improving the electrocaloric effect of a barium titanate-based ferroelectric perovskite electrocaloric material, characterized in that: Ba source, Sr source, Ca source, Hf source, Sn source, Zr source and Ti source are weighed and mixed evenly according to the stoichiometric ratio, and then pre-sintered to obtain (Ba x Sr y Ca z A 1-x-y-z )(Hf a Sn b Zr c Ti d B 1-a-b-c-d )O3 powder; after fine grinding and mixing with a binder, granulation is carried out, and then molding, aging, and plastic removal treatment are carried out to obtain a ceramic green body; finally, by sintering, a barium titanate-based ferroelectric perovskite electric caloric material with high electric caloric performance is obtained, wherein: 0.6≤x<1, 0<y≤0.4, 0<z≤0.4, 0<a≤0.3, 0<b≤0.3, 0<c≤0.3, 0.7≤d<1.

2. The method for improving the electrocaloric effect of barium titanate-based ferroelectric perovskite electrocaloric material according to claim 1, characterized in that: The Ba source, Sr source, Ca source, Hf source, Sn source, Zr source and Ti source are BaO, SrO, CaO or Ba(OH)2, Sr(OH)2 and Ca(OH)2.

3. The method for improving the electrocaloric effect of barium titanate-based ferroelectric perovskite electrocaloric material according to claim 1, characterized in that: The pre-sintering process is to heat the mixture in an oxygen, air or nitrogen atmosphere at 2-5°C / min. -1 The heating rate is raised to 1100-1400°C, kept warm for 1-6 hours, and cooled with the furnace.

4. The method for improving the electrocaloric effect of barium titanate-based ferroelectric perovskite electrocaloric material according to claim 1, characterized in that: The binder is polyvinyl alcohol, polyethylene glycol, polystyrene, methyl cellulose or a combination thereof, and its usage is 5-10wt% of the mass of the ceramic powder.

5. The method for improving the electrocaloric effect of barium titanate-based ferroelectric perovskite electrocaloric material according to claim 1, characterized in that: The aging refers to aging at room temperature for 22 to 48 hours.

6. The method for improving the electrocaloric effect of barium titanate-based ferroelectric perovskite electrocaloric material according to claim 1, characterized in that: The plastic removal refers to: in an oxygen or air atmosphere, at a temperature not higher than 2℃min -1 The heating rate is increased to 600-800°C and kept warm for 1-3 hours.

7. The method for improving the electrocaloric effect of barium titanate-based ferroelectric perovskite electrocaloric material according to claim 1, characterized in that: The sintering process is to heat the mixture in an oxygen, air or nitrogen atmosphere at 2-5°C / min. -1 The heating rate is increased to 1300-1500°C and kept warm for 1-6 hours. After sintering, the furnace is cooled to room temperature.

8. A barium titanate-based ferroelectric perovskite electrocaloric material prepared according to any one of claims 1 to 7, characterized in that: (Ba 0.8 Sr 0.199 Ca 0.001 )(Hf 0.025 Sn 0.025 Zr 0.025 Ti 0.925 )O3, (Ba 0.8 Sr 0.2 )(Hf 0.02 Sn 0.02 Zr 0.02 Ti 0.94 )O3, (Ba 0.8 Sr 0.199 Ca 0.001 )(Hf 0.03 Sn 0.03 Zr 0.03 Ti 0.91 )O3 or (Ba 0.905 Sr 0.09 Ca 0.005 )(Hf 0.0307 Sn 0.0307 Zr 0.0307 Ti 0.9079 )O3.

9. An application of the barium titanate-based ferroelectric perovskite electric caloric material prepared by the method according to any one of claims 1 to 7 or according to claim 8, characterized in that: It is used to prepare the electrode layer of solid-state refrigeration elements.

10. The use according to claim 9, characterized in that The surface of the barium titanate-based ferroelectric perovskite electrocaloric material is gold-plated by magnetron sputtering, and a gold electrode layer is obtained after deposition in a vacuum for 30 to 180 seconds at a current of 0.2 to 0.3 nA.

Citation Information

Patent Citations

  • Barium-titanate-based colossal-electrocaloric-effect chip-type laminate ceramic electrocaloric refrigeration device

    CN105236960A

  • Electrocaloric refrigeration device and refrigeration method

    CN111238077A

  • Barium strontium titanate-based energy storage ceramic material and preparation method thereof

    CN117735977A

  • Raw material powder for dielectric porcelain composition, and dielectric porcelain composition

    JP2001199765A

  • Process for preparing perovskite-type crystalline compound powders

    US20060045840A1